2023
DOI: 10.3390/app13105851
|View full text |Cite
|
Sign up to set email alerts
|

Synchronization of Surface Electromyography and 3D Electromagnetic Articulography Applied to Study the Biomechanics of the Mandible: Proof of Concept

Abstract: Background. The aim of this study was to propose and establish the proof of concept of an approach to synchronize 3D Electromagnetic Articulography (3D-EMA) with Surface Electromyography (SEMG) based on the standard components of this equipment. Methods. The appropriate equipment and instruments were selected according to specifications stablished for this study. Once the necessary equipment was gathered, the proper conditions to synchronize the signals were created. Thus, we selected a SEMG with a switch modu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 37 publications
(72 reference statements)
0
0
0
Order By: Relevance
“…Gómez et al [64] reported a protocol to simultaneously record electromyography (EMG) and electromagnetic articulography, which together with the previously presented variables provides a comprehensive examination of masticatory function. In a recent work, Lezcano et al [65] reported a recording protocol in which they synchronized the recordings of EMA and EMG.…”
Section: Electromyographymentioning
confidence: 99%
“…Gómez et al [64] reported a protocol to simultaneously record electromyography (EMG) and electromagnetic articulography, which together with the previously presented variables provides a comprehensive examination of masticatory function. In a recent work, Lezcano et al [65] reported a recording protocol in which they synchronized the recordings of EMA and EMG.…”
Section: Electromyographymentioning
confidence: 99%